Identification of factors that influence carbon emissions in tropical peatland - Yahya, Vanda Julita; Sabiham, Supiandi; Pramudya, Bambang; Las, Irsal (Universitas Jambi, 2019)
Abstract. The research aimed to find out the relationship between water table and soil as well as the influence of chemical (peat water content, pH) and physical (cation exchange capacity = KTK) factors on CO2 emission. The research used simple mathematic analysis using secondary data. The research was conducted in oil palm plantation in Koto Gasib districk, Siak Regency, Riau. Objects researched were water table level, rainfall and peatland chemical-physical factors in oil palm plantation. Research result indicated that rainfall and days of rain had linear relationship with water table level. Water table level contributed 71.48% to GRK emission and the remaining 28.52% was influenced by other factors. Peatland pH contributed 91.41% to emission, and the remaining 8.59% was influenced by other factors. The influence of KTK on emission was 88.66 % and the remaining 11.34% was influenced by other factors. Water content of peatland had influence on GRK emission of 96.19% and the remaining 3.81 % was influenced by other factors. Conclusion: water table level, water content, pH, and KTK had significant influence on CO2 emission. Research result shows that water content has the biggest influence on CO2 release compare to water table, KTK and pH.